Perception on the determinants of success: a case of small and medium enterprises (SMEs) manufacturing firms in Malaysia. - Yahya, A.Z.; Mahajar, A.J.; Othman, M.S. (2008)
The study attempted to identify factors that contributed to the establishment of successful businesses in Malaysia in particular those of Small and Medium Entrepreneurs (SMEs) manufacturing firms. The method is by using Koch’s 5 dimensions of success. The data for the study was collected through mail questionnaires sent to the selected SMEs. Of the total number 300 questionnaires mailed, 64 firms responded and completed the questionnaires. The empirical information resulted from analyzing the data obtained from the 64 SMEs suggests the following findings such as believing in God, experience, packaging of product, good internal control and having honest employees are among major factors that are vital to be possessed for those who intend to become as successful as existing SMEs manufacturing firms in Malaysia. Then, based on the result of this study, Koch’s 5 dimensions of success is being ranked.